If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 5 = -6x + -15 Reorder the terms: 5 + 4x = -6x + -15 Reorder the terms: 5 + 4x = -15 + -6x Solving 5 + 4x = -15 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 5 + 4x + 6x = -15 + -6x + 6x Combine like terms: 4x + 6x = 10x 5 + 10x = -15 + -6x + 6x Combine like terms: -6x + 6x = 0 5 + 10x = -15 + 0 5 + 10x = -15 Add '-5' to each side of the equation. 5 + -5 + 10x = -15 + -5 Combine like terms: 5 + -5 = 0 0 + 10x = -15 + -5 10x = -15 + -5 Combine like terms: -15 + -5 = -20 10x = -20 Divide each side by '10'. x = -2 Simplifying x = -2
| 9+1.88888888889-13=4 | | 4(3z+4)=2(6m+8) | | 9+5x=7x+12-2x | | 16x^2+121=0 | | -10x+9=50 | | -3/4=h/22 | | -4(3-t)=8(t+2) | | 0.05x=2.857x+0.06 | | 3/8(m+16)=9 | | 20x=2.857x+0.06 | | -20x=2.857x+0.06 | | 3.2+.17w=5.75 | | -14n+14n=-10 | | .70(x+100)+.10x=86 | | 3/8m+3=9 | | 2(2+.5l)=40 | | 3x/8+3/4=9 | | x+3-x-3=6 | | x+3-x-3= | | 6+3b=2 | | C(c+1)=1.10 | | 8=2g-12 | | 9=g-13 | | 15=g+9 | | 8f=f-28 | | 5f=f-24 | | 4+6(w-2)+w= | | 7(x)+9+3(x)+4=143 | | 2[w-(4w+9)+3]=2(w+6) | | 4f=f-6 | | -a=5/2-1/4(-6q+4) | | 9e=3e+12 |